The preparation of novel ion-exchange membranes by grafting of styrene onto pvdf and ptfe for application of polymer electrolyte fuel cells - Dương, Văn Đông (Trường Đại học Đà Lạt, 2012)
Proton conducting membranes for fuel cell applications have been prepared by grafting of styrene onto pre-formed fluoropolymer films using electron beam or gamma radiation and then sulfonated. The influence of the preparation conditions and the role of the initial fluoropolymer has been investigated. The investigation of PVDF and PTFE-graft-Styren films aimed to prepare the novel ion-exchanger and apply on electrolyte fuel cells. The grafting yields of PVDF and PTFE films gradually increased with the grafting time and then leveled off after 24 hours, which is independent of the irradiation condition. The concentration of free radical generated by Gamma-irradiation in PVDF and PTFE films increased with the irradiation dose in the range of 5 to 60 kGy. The free radicals generated in PVDF an d PTFE films decayed with storage time.